Parasite infection negatively affects PHA‐triggered inflammation in the subterranean rodent Ctenomys talarum. Issue 2 (31st December 2015) - Merlo, Julieta L.; Cutrera, Ana P.; Zenuto, Roxana R.
ABSTRACT: Magnitude and effectiveness of immune responses vary greatly between and within species. Among factors reported to determine this variation, parasitism is a critical one, although controversial effects of parasites over immunological indices have been reported. Information regarding immune strategies in species with different life histories is crucial to better understand the role of immune defenses in an ecological and evolutionary context. Here, we examine the influence of the parasite community on immune responsiveness of a solitary subterranean rodent, Ctenomys talarum . To do this, we assessed the impact of the natural parasite community and the experimental infection with Eimeria sp. on the phytohemagglutinin (PHA)‐response, as well as other immune, condition, nutrition, and stress parameters. PHA‐triggered inflammation was similarly impaired by Eimeria sp. infection alone or co‐occurring with a number of gastrointestinal nematodes. None of the other physiological parameters studied were affected by parasitism. This indicates that parasitism is a general key factor modulating immune responsiveness of the host, and in particular for C. talarum, it could explain the great inter‐individual variation previously observed in the PHA‐response. Thus, our results highlight the importance of taking the parasite community into account in ecoimmunological studies, particularly when using immunological indices. J. Exp. Zool. 9999A:XX–XX, 2015. © 2015 Wiley Periodicals, Inc.